#### Answer

x = -3
y = 9

#### Work Step by Step

x + y = 6; y=-3x
Substitute y for -3x to the first equation.
x -3x = 6
-2x = 6
x = -3 (divide both sides by -2 )
Substitute x=-3 to the second equation.
y = -3 $\times$ (-3)
y = 9

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

x = -3
y = 9

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.